Suppression of airway allergic eosinophilia by Hp‐TGM, a helminth mimic of TGF‐β. Issue 2 (12th July 2022) - Chauché, Caroline; Rasid, Orhan; Donachie, Anne‐Marie; McManus, Caitlin M.; Löser, Stephan; Campion, Tiffany; Richards, Josh; Smyth, Danielle J.; McSorley, Henry J.; Maizels, Rick M.
ABSTRACT: Type 2‐high asthma is a chronic inflammatory disease of the airways which is increasingly prevalent in countries where helminth parasite infections are rare, and characterized by T helper 2 (Th2)‐dependent accumulation of eosinophils in the lungs. Regulatory cytokines such as TGF‐β can restrain inflammatory reactions, dampen allergic Th2 responses, and control eosinophil activation. The murine helminth parasite Heligmosomoides polygyrus releases a TGF‐β mimic ( Hp‐ TGM) that replicates the biological and functional properties of TGF‐β despite bearing no structural similarity to the mammalian protein. Here, we investigated if Hp ‐TGM could alleviate allergic airway inflammation in mice exposed to Alternaria alternata allergen, house dust mite (HDM) extract or alum‐adjuvanted ovalbumin protein (OVA). Intranasal administration of Hp‐ TGM during Alternaria exposure sharply reduced airway and lung tissue eosinophilia along with bronchoalveolar lavage fluid IL‐5 and lung IL‐33 cytokine levels at 24 h. The protective effect of Hp‐ TGM on airway eosinophilia was also obtained in the longer T‐cell mediated models of HDM or OVA sensitisation with significant inhibition of eotaxin‐1, IL‐4 and IL‐13 responses depending on the model and time‐point. Hp‐ TGM was also protective when administered parenterally either when given at the time of allergic sensitisation or during airway allergen challenge. This project has taken the first steps in identifying the role of Hp ‐TGM in allergic asthma and highlighted its ability to control lung inflammation and allergic pathology. Future research will investigate the mode of action of Hp ‐TGM against airway allergic eosinophilia, and further explore its potential to be developed as a biotherapeutic in allergic asthma. Abstract : Type 2‐high asthma is a chronic inflammatory airway disease characterized by T helper 2 (Th2)‐dependent accumulation of eosinophils in the lungs. Regulatory cytokines such as TGF‐β can restrain inflammatory reactions, dampen allergic Th2 responses, and control eosinophil activation. The murine helminth parasite Heligmosomoides polygyrus releases a TGF‐β mimic ( Hp ‐TGM) that replicates TGF‐β properties despite bearing no structural similarity to the mammalian protein. Here we show that Hp‐TGM could alleviate airway and lung tissue eosinophilia, in association with control of IL‐5 and IL‐33 cytokine levels at 24 h, or either IL‐4 and eotaxin‐1, or IL‐4 and IL‐13 responses in T‐cell mediated models.